Measuring lens dimensionality in extreme scattering events through wave optics. Issue 3 (16th June 2022) - Jow, Dylan L; Pen, Ue-Li
ABSTRACT: Compact radio sources have been observed to undergo large, frequency-dependent changes in intensity due to lensing by structures in the interstellar medium, in so-called 'extreme scattering events' (ESEs). While the study of astrophysical plasma lensing has primarily focused on the geometric limit of optics, coherent radio sources such as pulsars exhibit wave effects when lensed. The additional phase information provided by interference effects in the wave regime may yield more information about the lens than could be obtained in the geometric regime. In this paper, we show that, using wave effects, one can potentially distinguish a one-dimensional lens (where 'one-dimensional' includes both highly elongated lenses, as well as perfectly axisymmetric lenses) from a fully two-dimensional lens, with minimal assumptions on the form of the lensing potential.